Chemical bath deposition-produced Ag2O nanoparticles synthesis and characterization for NO2 gas sensing applications - Khudadad, Ameer I. (Edelweiss Applied Science and Technology, 2025)
Deposition of thin films of silver oxide Ag2O of a nanoscopic nature, which are highly sensitive to NO2 gas, on quartz glass bases using the chemical bath deposition technique. Then conduct tests for pH values at the time of deposition at 75oC. In this work, AgNO3 was used. Through XRD examinations, the results showed that all the thin films are polycrystalline. Peaks of silver oxides such as Ag2O and AgO also appeared, with an average particle size ranging from 31.9 to 46 nm, depending on the sedimentation parameters. Also, through the use of (FESEM) electron microscopy technology, images of the samples used and the arrangement and distribution of the particles are shown. Using an atomic force microscope (AFM), the samples showed that the thin films were homogeneous with different surface roughness, and the particle size ranged from 55.57 to 87.1 nm. It was noted that Ag2O films have a high sensitivity of approximately 71.58 to NO2 gas at an operating temperature of 75oC. The study showed that it is possible to manufacture high-quality and efficient gas sensors from silver oxide nanoparticles.